Job Satisfaction among Women Teachers in Purba Medinipur District of West Bengal: An Assessment - Maiti, Mr. Dilip (International Journal on Integrated Education, 2023)
A teacher's optimistic outlook is crucial in the classroom. In order to find fulfillment in their profession, teachers must be able and willing to do their duties with the highest dedication. Feeling emotionally and mentally fulfilled in one's work is what we call "job satisfaction. In this study an attempt has been made to find out the job satisfaction among women teachers in Purba Medinipur, West Bengal, to find out the job satisfaction among women teachers in respect of age group, Educational Qualification and teaching experience. For this purpose a sample of 480 women teachers have been selected randomly from Purba Medinipur district. Job Satisfaction Scale Dr. A. R. Annamalai's (1998) Job Satisfaction Scale was employed. There are 40 questions on the teacher work satisfaction scale, each with five possible answers. One of these concerns the happiness of female educators in their jobs. The final score is the sum of all the individual point totals. Findings of the study indicate that Women teachers of Purba Medinipur district have high level of job satisfaction and age does not matter in the job satisfaction of women teachers.